Association of CCR5Δ32 with reduced risk of childhood but not adult asthma. Issue 3 (1st March 2003) - Srivastava, P; Helms, P J; Stewart, D; Main, M; Russell, G
Abstract : Background: A number of potential candidate genes have been implicated in the pathogenesis of asthma. A 32 base pair deletion in the CCR5 gene renders this chemokine receptor non-functioning and has been shown to be associated with a reduced prevalence of asthma in childhood. The mechanism may be related to impairment of pathogen entry into cells and modified host inflammatory response. We sought to determine the influence of the CCR5Δ32 mutation on asthma and allergy in the transition from childhood to adulthood. Methods: 627 individuals first studied as part of a whole population schoolchildren cohort in 1989 when aged 8–12 years were followed up 10 years later for respiratory and allergy symptoms and laboratory markers of atopy. CCR5Δ32 status was also characterised and the association with childhood and adulthood symptoms determined. Results: The follow up sample was representative of the original cohort except for a slightly greater prevalence of symptomatic individuals. As children, none who were homozygous for the CCR5Δ32 mutation had a current physician's diagnosis of asthma. In multivariate analysis and controlling for known confounders, the protective effect of carrying the allele in childhood was highly significant (OR 0.31, 95% CI 0.14 to 0.72, p=0.006). There was no protective association with "current asthma" as classified in adulthood within the same population. Subjective or laboratory markers of atopy in childhood or adulthood were not associated with the CCR5Δ32 mutation. Methacholine bronchial hyperresponsiveness in adulthood was also unrelated to gene carrier status. Conclusions: In a population with a high allelic frequency for the CCR5Δ32 mutation, a significant protection against childhood asthma is evident which is independent of atopy. This protection is lost in the transition between childhood and early adulthood. The contribution of different genetic candidates to the expression of asthma may change with advancing maturity and confound the interpretation of association and linkage studies unless age is taken into account.